(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
. The article discusses the key philosophical values of modernity that reflect the changing priorities and challenges of our time. The author analyzes the influence of technology and social changes on public consciousness and the value orientations of individuals. In the context of the rapid development of information technologies and social networks, philosophical ideas become important tools for understanding new realities and forming ethical norms. Topics such as different schools of thought, from existentialism to humanism, are discussed, offering various answers to questions about the meaning of life, freedom of choice, and responsibility. The author also emphasizes how philosophical ideas can assist in addressing pressing global issues, such as ecological crises, social justice, and inequality. The article raises questions about the role of philosophy in shaping critical thinking and the ability to engage in constructive dialogue, which is particularly important in the context of polarized opinions and conflicts. In conclusion, the author underscores the importance of dialogue between different philosophical schools and cultures in forming a comprehensive understanding of values that contribute to the harmonious development of society. Such dialogue can serve as a foundation for creating more sustainable and just social structures, where philosophical values guide decision-making at all levels—from the individual to the global.